2010
DOI: 10.1111/j.1365-2494.2010.00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of defoliation frequency and cutting height on growth, dry‐matter yield and nutritive value of Napier grass (Pennisetum purpureum (L.) Schumach)

Abstract: Growth characteristics, dry-matter (DM) yield, chemical components and in vitro dry-matter digestibility (IVDMD) of Napier grass were studied in a randomized complete block design with three replications at Haramaya University, Ethiopia. The treatments were three defoliation frequencies (60, 90 and 120 d after Napier grass establishment) and five cutting heights (5, 10, 15, 20 and 25 cm above ground level). Except for leaf-to-stem ratio, all growth characteristics increased with decreasing frequency of defolia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
36
0
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 31 publications
8
36
0
10
Order By: Relevance
“…The value of stem/leaf was an important index of forage quality, intake, and diet selection [27], usually the value was smaller and the nutrition was higher, because leaf contains more nutrition and is more palatable than stem [28] [29].…”
Section: Harvesting Biomass At Middle August In the Second Yearmentioning
confidence: 99%
“…The value of stem/leaf was an important index of forage quality, intake, and diet selection [27], usually the value was smaller and the nutrition was higher, because leaf contains more nutrition and is more palatable than stem [28] [29].…”
Section: Harvesting Biomass At Middle August In the Second Yearmentioning
confidence: 99%
“…Entretanto, DAHER, et al (2004) verificaram correlação inversa entre as características diâ-metro do colmo e produção de matéria seca. Além disto, a relação colmo/folha afeta os teores de fibra, influenciando tanto na digestibilidade quanto no poder calorífico (TESSEMA et al, 2010;XIA et al, 2010;QUEIROZ FILHO et al, 2000). No presente estudo, os genótipos foram separados de acordo com Skott Knott (P<0,05) em dois grandes grupos na primeira, segunda e quarta avaliações, enquanto na terceira e quinta três grupos foram formados.…”
Section: Agrupamento De Médiasunclassified
“…De modo geral, com o aumento do intervalo entre os cortes os teores de proteína, hemicelulose e a digestibilidade da biomassa decrescem, enquanto os de fibra, lignina e celulose, bem como a produtividade aumentam. Portanto, intervalos maiores entre cortes devem ser adotados para uso na produção de energia e intervalos menores para uso na alimentação animal (FLORES et al, 2012;KANNIKA et al, 2011;TESSEMA et al, 2010). Independente da forma de utilização pretendida a elevada produtividade de biomassa é desejada, e algumas características morfológicas do capim-elefante são altamente correlacionadas com a produção de biomassa (XIA, 2010;DAHER et al, 2004).…”
unclassified
“…Other studies using ILRI accessions (Ansar et al, 2010;Tessema et al, 2010) showed that their biomass production is influenced by the environment and management, in addition to other traits inherent in the accessions.…”
Section: Dry Matter Yieldsmentioning
confidence: 99%